ANALYSIS AND KINETIC STUDY ON EXTRACTION PROCESS OF CELLULOSE FROM PLANT-BASED MATERIALI - NURSHUHADA, GARIP (Universiti Malaysia Sarawak, (UNIMAS), 2020)
This study aimed to evaluate the extraction of cellulose from plant-based materials including the analysis on parameters affecting the extraction process and the kinetic study on the yield of cellulose extracted from lignocellulosic biomass. Cellulose is the most abundantly available organic matter on earth, which can be derived from various sources. Lignocellulosic biomass materials are receiving increased attention as an economical, abundant, and renewable alternative for the production of various value-added products. Various conversion technologies are used for the production of value-added products from biomass, including chemical treatment, physical treatment, etc. Pretreatment plays a critical role in the yield of the products. The effect of extraction parameters on the pretreatment of plant fibres was described in this study. The results showed that temperature, alkali treatment, and extraction time have a significant effect on the yield of cellulose obtained. Also, the applicability of different mathematical models (Peleg and Page models) to describe the kinetics of the extraction process of cellulose from plant materials was studied as well. The study was performed in order to select the most suitable model to describe the kinetics of the extraction process of cellulose. Mathematical modelling is an extremely useful engineering tool that helps to study the effect of various parameters together with making behaviours predictions for future applications. The mathematical models applied showed a good agreement with the experimental result, and Peleg model showed the best fitting results compared to other models. Validation of the kinetic models was based on the determination of coefficient (R2), and root mean square error (RMSE). Peleg’s model with the highest R2 (0.998) and the lowest average value of RMSE (0.2265) was determined to be the most suitable model to describe the extraction process of cellulose.